The Wealth of (Open Data) Nations? Examining the Interplay of Open Government Data and Country-level Institutions for Entrepreneurial Activity at the Country-level - Ponce, Alan (2020)
https://papers.ssrn.com/sol3/papers.cfm?abstract_id=3667896